Importance of preoperative total colonoscopy and endoscopic resection after self-expandable metallic stent placement for obstructive colorectal cancer as a bridge-to-surgery - Shuichi Itonaga; Shohei Hamada; Eikichi Ihara; Hitoshi Honma; Hiroki Fukuya; Akito Ookubo; Taisuke Sasaki; Daisuke Yoshimura; Makoto Nakamuta; Yorinobu Sumida; Naohiko Harada (BMC Gastroenterology, 2023)
Abstract Background and aim Colonic self-expandable metallic stent (SEMS) placement enables preoperative total colonoscopy (TCS) in patients with obstructive colorectal cancer. Following SEMS placement, it is possible to assess the presence or absence of synchronous proximal colon cancers and perform preoperative endoscopic resection (ER) for neoplastic lesions proximal to the primary lesion. The objective of this study was to determine the usefulness and safety of preoperative TCS and ER after SEMS placement in patients with obstructive colorectal cancer. Methods From April 2016 to March 2022, we enrolled 100 patients with obstructive colorectal cancer who underwent SEMS placement, including 86 patients who underwent preoperative TCS after SEMS placement. Complications associated with preoperative TCS and ER after SEMS placement and the characteristics of the neoplastic lesions were assessed. Results The success rate of SEMS placement as bridge-to-surgery was 98.0%; six patients had associated complications. Preoperative TCS was performed 8 (range: 1–30) days after SEMS placement. Four patients had synchronous advanced cancers. Nine non-advanced synchronous cancers, 116 adenomas, and 18 sessile-serrated lesions were treated by preoperative TCS and ER after SEMS placement. No procedure-related complications, namely stent migration, bleeding, and perforation were observed. Forty-five patients underwent follow-up TCS 1 year after surgery. Only one patient with submucosal invasive cancer required a second surgery. Conclusions Preoperative TCS and ER after SEMS placement was performed with no complications. This approach allows preoperative evaluation of the entire colon and the treatment of precancerous lesions. (240 words)